2016
DOI: 10.4314/njtd.v13i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of locust bean pod solution (LBPS) in the production of sandcrete blocks for buildings

Abstract: Locust beam pod solution (LBPS) was prepared by extraction from the outer leathery cover of the pod soaked in water for twenty four hours in ten different concentrations of known weight of dried locust bean pod cover in 20 litres of clean water. Using ten levels of these concentrations, five sandcrete blocks of size 150mm cube were produced for each concentration, making a total of fifty blocks and the compressive strengths at 28 days were determined. Using a concentration of 50g/l, twenty blocks were produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The locust bean pods are waste obtained from the African locust bean tree "Parkiabiglobosa" which is a perennial legume tree and grows in the savannah zone of West Africa [4,5] with the pulp separated from the pod and burnt to obtain LBPA. Numerous researchers have employed several materials as substitute for cement such as palm oil husk ash (POHA), pulverized fly ash (PFA) [6], rice husk ash (RHA) [7], coconut husk ash (CHA) [8], eggshell powder ash [9,10], locust bean pod ash [10] and etc.…”
Section: Introductionmentioning
confidence: 99%
“…The locust bean pods are waste obtained from the African locust bean tree "Parkiabiglobosa" which is a perennial legume tree and grows in the savannah zone of West Africa [4,5] with the pulp separated from the pod and burnt to obtain LBPA. Numerous researchers have employed several materials as substitute for cement such as palm oil husk ash (POHA), pulverized fly ash (PFA) [6], rice husk ash (RHA) [7], coconut husk ash (CHA) [8], eggshell powder ash [9,10], locust bean pod ash [10] and etc.…”
Section: Introductionmentioning
confidence: 99%
“…The fruit husks extract has been used as a bonding agent between locally manufactured clay tiles and the soil beneath [10]. The decoction has been used on floors, walls of rooms, and in soil constructions in West Africa to improve their durability, [11] [12] to the production of laterite blocks for buildings to prove their durable protection and waterproofing [13] [14]. Scientific works had shown that they can be used as biopesticides in soils [15] [16].…”
Section: Introductionmentioning
confidence: 99%
“…The plant increases soil fertility, grows to about 20 to 30 m in height and has dark, evergreen, pinnate leaves. Its fruit is a brown, leathery pod of about 10 to 30 cm long and contains gummy pulp of an agreeable sweet taste, in which there is a number of seeds (Aguwa et al, 2016). It is found in a wide range of environment in Africa and primarily grown for its pods that contain both sweet pulp and valuable seeds.…”
Section: Introductionmentioning
confidence: 99%
“…The seeds of the locust bean are used for food seasoning in almost all parts of Nigeria and are popularly known as Dawadawa in northern Nigeria while the Yorubas call it iru. The seeds are used extensively as seasoning and nutritious additives to soups and stews as well as a good source of essential amino acids (Aguwa et al, 2016). Every part of the plant (leaves, flowers, seeds, roots and bark) can be used as food and have been found to be medicinal and therapeutic in nature (Okuda et al, 2000).…”
Section: Introductionmentioning
confidence: 99%